Knowledge and awareness of food safety among middle school students in Tripoli, Libya (Journal of Patan Academy of Health Sciences, 2021)
Introduction: To protect public health in society, it is imperative to promote good food safety practices by raising awareness and knowledge, especially among school students. This study aimed to assess the food safety knowledge and practices among middle school students in Tripoli, Libya.Methods: The study was conducted through a questionnaire to find out the level of food safety knowledge and practices among randomly selected students from several municipalities in Tripoli city, Libya, from May to November 2019. Approval from the director of the Basic Education Administration was taken. Data were analyzed to determine the association of demographics and the level of knowledge and practices, the correlation between knowledge and practice scores. The data analysis was performed by SPSS. A Chi-square test was used to find out the association. A p